AUDIT DELAY PADA PERUSAHAAN PERTAMBANGAN : ANALISIS DAN FAKTOR-FAKTOR PENENTUNYA - Liki Melati; Ardiani Ika Sulistyawati (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2016)
This study aimed to analyze the effect of firm size, firm size, solvency, and profitability to the audit delay. This study uses secondary data obtained from the Indonesia Stock Exchange. This population is a mining company listed on the Indonesia Stock Exchange during 2012-2014 period as many as 12 companies. The samples in this study using purposive sampling method. Performed during the observation period of 3 (three) years ie 2012-2014.Data analysis method used is multiple linear regression analysis. The results of the research that company size and profitability significantly influence audit delay. While the size of the firm and the solvency does not significantly influence audit delay.